Review of adult gender transition medications: mechanisms, efficacy measures, and pharmacogenomic considerations - Sehgal, Inder (Frontiers in Endocrinology, 2023)
Gender dysphoria is the imparity between a person's experienced gender and their birthassigned gender. Gender transition is the process of adapting a person's sexual characteristics to match their experienced gender. The number of adults receiving sex hormone therapy for gender dysphoria is increasingly and these pharmacotherapies are increasing being prescribed in a general practice setting. The role of hormone therapy is to reverse or reduce physical sexual characteristics of the birth-assigned gender and enhance and build characteristics aligning to the expressed gender and t. hese therapies apply to both transgender and gender nonconforming patients. Recognizing the options and interpreting the effects of gender transition therapies are fundamental to the discussion and treatment of gender dysphoria. This review summarizes pharmacodynamics, comparative dosing, adverse effects, monitoring, and potential pharmacogenetic influence of current pharmacotherapy. These include the use of 17beta-estradiol, spironolactone, testosterone, GnRH agonists as well as adjunctive phosphodiesterase-5 inhibitors. The article also addresses gaps within the published literature including optimal routes of administration for individual patients, risks of malignancy and dosing reductions as transgender patients age.